Evaluación del aporte de carga contaminante de la quebrada El Quince a la laguna de Yahuarcocha - Chamorro Freire, Dennis Alexander (2022)
At present, the increase in rural population areas and the expansion of the agricultural and livestock frontier has given way to an increase in polluting causes with effects on the water area of the El Quince creek, affecting said resource in its physical and chemical, as well as in the decrease of the ecological flow that it contributes to the Yahuarcocha lagoon, disturbing the health and maintenance of aquatic ecosystems, in the same way causing the decrease of the body of water. The present investigation presented a study of the description of the soil, through thematic maps, with the help of the ArcGis computer system, coordinates of the sampling points and topographic maps obtained from the Ecuador geo-portal\; as well as the results of the analysis of land use, corresponded to the activity with the greatest influence, which is agricultural production, with corn monocultures causing a proliferation of pollutants. The evaluation of the water quality index, characterization of land use and the calculation of the ecological flow of this stream were also determined. For the analysis of the water quality index, the Brown parameters were taken as a reference: Fecal Coliforms, Hydrogen Potential (pH), Biochemical Oxygen Demand (BOD5), Nitrates (NO3), Phosphates (PO4), Temperature, Turbidity, Solids total dissolved and dissolved Oxygen, which helped to classify the water into five ranges: Excellent, Good, Regular, Bad and Very Bad. Having as a result the water quality of the El Quince creek, it is in the Regular range. In the study of the ecological flow that enters the Yahuarcocha lagoon, the Texas method was implemented, in the period March-October, in which the ecological flow that enters the lagoon is 60% of the monthly flow, establishing ourselves as result of 0.06 m3/s of ecological flow of water.